The Practice of Human Development and Dignity - Sedmak, Clemens, 1971-; Carozza, Paolo G. (Book collections on Project MUSE., 2020)
Although deeply contested in many ways, the concept of human dignity has emerged as a key idea in fields such as bioethics and human rights. It has been largely absent, however, from literature on development studies. The essays contained in 'The Practice of Human Development and Dignity' fill this gap by showing the implications of human dignity for international development theory, policy, and practice. Pushing against ideas of development that privilege the efficiency of systems that accelerate economic growth at the expense of human persons and their agency, the essays in this volume show how development work without sensitivity to human dignity is blind. Rather, genuine development must advance human flourishing and not only promote economic betterment. At the same time, the essays in this book also demonstrate that human dignity is an empty concept considered apart from real human experiences and practices. This volume therefore considers the meaning of human dignity inductively in light of development practice, rather than simply providing a theory or philosophy of human dignity in the abstract. It asks not only "what is dignity" but also "how can dignity be done?"0Through a unique multidisciplinary dialogue, 'The Practice of Human Development and Dignity' offers a dialectical and systematic examination of human dignity that moves beyond the current impasse in thinking about the theory and practice of human dignity. It will appeal to scholars in the social sciences, philosophy, and legal and development theory, and also to those who work in development around the globe.